Performance estratégica y económica de empresas estatales: el caso de las aerolíneas latinoamericanas - Gallegos Monteagudo, Armando (Universidad ESAN. ESAN Ediciones, 1992)
Seeks to develop new methods to identify objectives and evaluate the performance of state-owned companies, as well as to compare their performance with that of private companies. Comprises the operations between 1981 and 1987 of 17 airlines classified as: public Latin American, private Latin American and North American with operations in Latin America. First, the Delphi method is applied to identify the objectives and criteria for evaluating the performance of public airlines. Secondly, new methods for performance evaluation are evaluated using Data Envelopment Analysis. The third part is devoted to comparative performance studies and their implications for management and public policy formulation; the tools developed in the previous stages are used to relate ownership, international competition and efficiency. The results of the study indicate that the privatization strategies applied may produce some, but modest, efficiency gains. More fruitful might be to consider other strategies that allow moving up the entire efficiency frontier, such as some deregulation of domestic and international markets.

Busca desarrollar nuevos métodos para identificar objetivos y evaluar el desempeño de las empresas estatales, así como comparar su desempeño con el de las empresas privadas. Comprende las operaciones entre 1981 y 1987 de 17 aerolíneas clasificadas en: públicas latinoamericanas, privadas latinoamericanas y norteamericanas con operaciones en América Latina. En primer lugar, se aplica el método Delphi para identificar los objetivos y criterios para evaluar el desempeño de las aerolíneas públicas. En segundo lugar, se evalúan nuevos métodos de evaluación del desempeño mediante el análisis envolvente de datos. La tercera parte está dedicada a los estudios comparativos de desempeño y sus implicaciones para la gestión y formulación de políticas públicas; Las herramientas desarrolladas en las etapas anteriores se utilizan para relacionar propiedad, competencia internacional y eficiencia. Los resultados del estudio indican que las estrategias de privatización aplicadas pueden producir algunas, aunque modestas, ganancias de eficiencia. Podría ser más fructífero considerar otras estrategias que permitan avanzar en toda la frontera de la eficiencia, como cierta desregulación de los mercados nacionales e internacionales.
Keywords: Performance; Public firms; Desempeño; Private firms; Empresas públicas; Empresas privadas; Public politics; Política pública; https://purl.org/pe-repo/ocde/ford#5.02.04